Therapeutic Communication as an Effort to Increase Rehabilitation Motivation for Female Drug Users at the Cahaya Putra Selatan Foundation, Palembang - Dewi Sartika; Henny Yusalia; Muhammad Arif Setiawan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research is motivated by the complexity of the rehabilitation process among female drug users, which is influenced by psychological, social, and stigma-related factors, thereby affecting the dynamics of motivation in undergoing rehabilitation. This study aims to analyze the process of therapeutic communication in enhancing rehabilitation motivation and to identify the barriers faced by female drug users at Yayasan Cahaya Putra Selatan Palembang. This research employs a qualitative method with a descriptive approach. Data were collected through non-participant observation, in-depth interviews with the program manager, counselors, female clients, religious figures, and police officers, as well as documentation. The data were analyzed using thematic analysis. This study applies Symbolic Interactionism Theory and Self-Determination Theory (SDT). The findings show that therapeutic communication occurs gradually through empathetic and non-judgmental relationships that build trust, which then develops through individual and group counseling to encourage openness, reflection on experiences, and changes in clients' self-perception, leading to the formation of rehabilitation motivation over time. However, the process faces internal barriers such as emotional resistance, shame, and negative self-concept, as well as external barriers including lack of family support, economic pressure, parental responsibilities, and social stigma